QR Code-Based Smartbox Media Innovation: Encouraging Generation Alpha to Improve Learning Outcomes - Eva Fadhillah; Emy Yunita Rahma Pratiwi (JURNAL PENDIDIKAN DASAR NUSANTARA, 2026)
This study aims to develop a QR Code-based Smartbox media and determine the level of validity, practicality, and effectiveness of QR Code-based smartbox media in improving the learning outcomes of the Alpha generation in Pancasila Education learning. This study uses a research and development method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of the study were second-grade elementary school students in three schools, namely SDN Badas 2 Kediri, SDN Plandi 1 Jombang, and SDN Sengon Jombang. The research instruments included expert validation sheets, teacher and student response questionnaires, and learning outcome tests in the form of pretests and posttests. Data analysis was carried out using descriptive and quantitative analysis, including paired samples t-tests and N-Gain analysis. The results showed that the QR Code-based Smartbox media was declared valid and practical, and effective in improving student learning outcomes. This was indicated by the significance value of the t-test results which was smaller than 0.05. Thus, QR Code-based Smartbox media is suitable for use as an alternative innovative learning media that is in accordance with the characteristics of the Alpha generation and supports the implementation of student-centered learning.